2013
DOI: 10.1530/eje-13-0306
|View full text |Cite
|
Sign up to set email alerts
|

Higher free thyroxine levels are associated with all-cause mortality in euthyroid older men: the Health In Men Study

Abstract: Objective: Thyroid dysfunction predicts poorer health outcomes, but the relationship between thyroid hormone levels within the reference range and mortality in older adults remains unclear. In this study, we examined the associations between the concentrations of free thyroxine (FT 4 ) and TSH and allcause mortality in older men without thyroid disease. Subjects and methods: We performed a longitudinal study in community-dwelling men aged 70-89 years. Men with thyroid disease or taking thyroid-related medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 41 publications
4
48
0
3
Order By: Relevance
“…It has been recently reported that all-cause mortality is associated with higher FT4 but not TSH variations in euthyroid elderly men. 30 The current study differs from that study on several points. First, only men were examined in that study, so it is difficult to draw any conclusions for the general population.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been recently reported that all-cause mortality is associated with higher FT4 but not TSH variations in euthyroid elderly men. 30 The current study differs from that study on several points. First, only men were examined in that study, so it is difficult to draw any conclusions for the general population.…”
Section: Discussionmentioning
confidence: 64%
“…It has been recently reported that in euthyroid elderly men all-cause mortality is associated with higher FT4 but not TSH variations (30). Our study differs from the study reported above in several points.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines specifically recommend (recommendation 15) that the oldest old subjects (>80-85 years) with elevated serum TSH ≤10 mU/l should be carefully followed with a wait-and-see strategy, generally avoiding hormonal treatment. This procedure is supported by a recent study showing that older patients are at particular risk for overtreatment, as their upper limit of normal for the level of TSH is slightly higher than that in younger patients [7]. Among 3,900 community-dwelling apparently euthyroid Caucasian Australian men over 70 years of age, those whose free thyroxine was normal but in the highest quartile were 20% more likely to have died over 6 years of follow-up.…”
mentioning
confidence: 78%
“…In another study by Murphy et al, evaluating 1278 healthy euthyroid postmenopausal women, higher FT4 within the normal range was associated with lower hip bone mineral density, increased bone loss and non-vertebral fracture risk (75). In a cohort of 3485 euthyroid men aged 70-89 years from the Health In Men Study, higher FT4 levels were found to be associated with all-cause mortality, independently of conventional risk factors and medical comorbidities (76). Noteworthy, in the same cohort from the Health In Men Study, higher FT4 was an independent and significant predictor of frailty, suggesting that circulating FT4, even within the normal range, might contribute to weight loss and reduced physical capability (70).…”
Section: Thyroid Status Morbidity and Mortality In The Elderlymentioning
confidence: 97%